The development of affective assessment instruments in the new normal era (post-covid-19) - Mu'ammar, Muhammad Arfan; Sofandi, Aris (ATTARBIYAH: Journal of Islamic Culture and Education, 2022)
This development research was conducted at MTs Ma'arif Ketegan Sidoarjo. The types of data obtained are qualitative and quantitative data. The survey results showed that 50% of teachers developed their own affective assessment instruments but 87.5% of teachers admitted that these instruments were not valid and reliable. Then as many as 81.3% of teachers chose to use the observation method in assessing student effectiveness during online learning, because it is considered the easiest. As many as 62.5% of teachers do not understand that affective assessment of students in online learning can be done using the self-assessment method. The instrument is presented in a Google Form which contains 50 contextual statement points with a Likert Scale. The content validation score with the Aiken's V formula obtained a score of less than 1 for each statement item. Construct validation is a follow-up to the input of the supervisor and the theory that has been analyzed. External validation shows an increase in instrument models that are more applicable and adaptive. Instrument stability obtained a score of 0.885 so it was concluded that it was less reliable for a significant level of 1% and reliable for a significant level of 5%. The instrument equivalence data shows that there is no significant change in the results of the original and alternative instruments. Internal consistency with the Cronbach Alpha coefficient obtained a score of 0.92 with a very high category. The instrument also has a practical and efficient title. Thus this instrument is considered valid, reliable, useful, and valid. The response given by this instrument is said to be valid, reliable, practical and valid.